Julie is asked to solve the system below by elimination. Which of the following steps would be the best way to begin?

the system: 2x+y=-3 3x-2y=2

1 answer

To solve the system by elimination, you need to eliminate one variable by manipulating the equations. Here's one possible way to begin:

1. Multiply the first equation by 2 to make the coefficients of y in both equations equal:
2 * (2x + y = -3) = 4x + 2y = -6

2. Now, add this modified equation to the second equation:
(4x + 2y) + (3x - 2y) = -6 + 2
Simplifying, you get:
7x = -4

This step helps in eliminating the y variable.